Revisión taxonómica del género Hypseocharis en Perú y Bolivia - Lozada-Gobilard, Sissi (2020)
In the present study we revised the genus Hypseocharis in Bolivia and Peru. A total number of 105 herbarium specimens were revised to evaluate the morphological diversity across the range of the genus. In a subset of 24 complete individuals a multivariate morphometric analysis was performed to evaluate the morphological characters historically used to differentiate the “species” of the genus Hypseocharis. A revision of the herbarium material indicated that there are no sharp lines dividing the different “species” with the only exception of H. tridentata. The multivariate analysis indicated that H. bilobata, H. malpasensis and H. pedicularifolia all occupy the same morphospace as H. pimpinellifolia and there are no individual morphological characters or suites of characters permitting the differentiation of distinct taxa. This confirms earlier findings from Argentina: There are only two species in the genus, widespread Hypseocharis pimpinellifolia and H. tridentata. Hypseocharis pilgeri, originally described from Peru, can also not be differentiated from H. pimpinellifolia. We propose the recognition of only two species: H. pimpinellifolia with variously pinnate to bipinnate leaves with a terminal leaflet at most marginally larger than the lateral ones, flowers with 15 anthers and capsular fruits as differing from H. tridentata with pinnate leaves with the terminal leaflet much larger than the lateral ones, flowers with 5 anthers and schizocarpic fruits. Hypseocharis pimpinellifolia is a widespread and polymorphic species, ranging from Ancash (Peru) to La Rioja (Argentina) and comprises forms with white, yellow, orange, and red corollas and with simply pinnate to very finely bipinnate leaves.